2020
DOI: 10.1371/journal.pone.0226814
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gridded precipitation datasets for rainfall-runoff and inundation modeling in the Mekong River Basin

Abstract: Precipitation, as a primary hydrological variable in the water cycle plays an important role in hydrological modeling. The reliability of hydrological modeling is highly related to the quality of precipitation data. Accurate long-term gauged precipitation in the Mekong River Basin, however, is limited. Therefore, the main objective of this study is to assess the performances of various gridded precipitation datasets in rainfall-runoff and flood-inundation modeling of the whole basin. Firstly, the performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 36 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…To evaluate the performance of annual maximum inundation, the threshold of inundation depth of 0.5 m was selected following previous studies (Sayama et al, 2012, 2015; Try et al, 2020; Try, Lee, Yu, et al, 2018) to identify the flooded and non‐flooded areas. The statistic indices of observation and model prediction flood extent for 8 years (2000–2007) were calculated (see Figure 4 for the comparison map of simulation and observation).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate the performance of annual maximum inundation, the threshold of inundation depth of 0.5 m was selected following previous studies (Sayama et al, 2012, 2015; Try et al, 2020; Try, Lee, Yu, et al, 2018) to identify the flooded and non‐flooded areas. The statistic indices of observation and model prediction flood extent for 8 years (2000–2007) were calculated (see Figure 4 for the comparison map of simulation and observation).…”
Section: Resultsmentioning
confidence: 99%
“…The topographic information was derived from the MERIT DEM (Yamazaki et al, 2017) by scaling up from 3‐arc second (~90 m) to 5‐arc minute (~10 km) for the whole MRB simulation and 60‐arc second (~2 km) for the LMB. Try et al (2020) suggested that the Global Precipitation Climatology Centre (GPCC) product is suitable for long‐term hydrological modelling in the MRB. Therefore GPCC precipitation was used for long‐term verification in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be achieved through imputing missing data [60], interpolating additional stations from gridded data [37], or substituting station data with gridded observations [61]. While there has been a substantial improvement of gridded datasets, few studies to have utilised gridded observations have either supplemented with station data or used coarse resolution gridded datasets [37,61,62]. This study seeks to test the performance of the highresolution (0.05 • ,~5.55 km) Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) [63] and CHIRTS (Temperature) [64] datasets as an alternative to station data in hydrological simulations and utilise them to assess the long-term impacts of LULC on the surface runoff response in a dynamic tropical urban watershed and downscale future climate simulations.…”
Section: Introductionmentioning
confidence: 99%